Computational Study of Interstitial Hydrogen Atoms in Nano-Diamond Grains Embedded in an Amorphous Carbon Shell (Communications in Computational Physics, 2011)
The properties of hydrogen atoms in a nano-diamond grain surroundedby an amorphous carbon shell are studied with Tight Binding computer simulations.Our samples model nano-diamond grains, of a few nanometers in size, that nucleatewithin an amorphous carbon matrix, as observed in deposition from a hydrocarbonrich plasma. The calculations show that the average hydrogen interstitial formationenergy in the amorphous region is lower than in the nano-diamond core, thereforehydrogen interstitial sites in the in the amorphous region are more stable than in thenano-diamond core. This formation energy difference is the driving force for the diffusionof hydrogen atoms from nano-diamond grains into amorphous carbon regions.An energy well was observed on the amorphous side of the nano-diamond amorphouscarbon interface: hydrogen atoms are expected to be trapped here. This scenario agreeswith experimental results which show that hydrogen retention of diamond films increaseswith decreasing grain size, and suggest that hydrogen is bonded and trappedin nano-diamond grain boundaries and on internal grain surfaces.